The application of 3D printed self-glazed zirconia for full-mouth rehabilitation in a patient with severely worn dentition: a case report. (17th August 2020) - Huang, Zhu; Huang, Jiangyong; Li, Chanxiu; Shi, Andi; Wu, Jingwen; Ren, Wen; Liang, Tingting; Li, Fuyao; Li, Yuanjing; Yang, Li; Liu, Tiantao; Jiang, Qianzhou; et al.
ABSTRACT: This clinical case report describes the fabrication of monolithic self-glazed zirconia prostheses via a digital workflow, for full-arch rehabilitation in a patient with a severely worn dentition. Prostheses composed of self-glazed zirconia are less prone to chipping, and have a lower risk of progressive wear of the opposing natural teeth. The use of a digital workflow not only ensures a higher degree of precision in the fabrication of self-glazed zirconia prostheses, but it also greatly improves patient comfort, and reduces the clinical chairside time required for adjustments.